TUTANKHAMUN And the Golden Treasures of Ancient Egypt - Lewis, Brenda Ralph, author 644291; Shaw, Ian, 1944-, editor 198047 (London : Star Fire, 2007)
The discovery of Tutankhamun's tomb in 1922 is one of the most famous archaelogical events of the twentieth century and accounts for much of the Pharaoh's popularity. But how much have we seen of what was discovered there and in other tombs and temples? Now, with fascinating text and revealing illustrations, learn about the world of the ancient Egyptians from their huge variety of beautiful and skilled artefacts and artworks, from mummies, coffins and statues to jewelery, gold and woodwork.